Effect of Verbal Feedback in Twelve Weeks Handball Training on Self-Efficacy and Life Satisfaction - TOROS, Turhan (Asian Journal of Education and Training, 2018)
The aim of this study was investigate the effect of verbal feedback on self-efficacy and life satisfaction. A total of 30 students as experimental group (n=15, mean age= 20.13±1.79) and control group (n=15, mean age=20.57±1.62) with similar characteristics were included in the study. Self-efficacy scale that originally developed by Riggs et al. (1994) and adapted to Turkish population by Öcel (2002) and life satisfaction scale that originally developed by Diener et al. (1985) and adapted to Turkish population by Yetim (1991) were used. Shapiro-Wilk test was interpreted for normality in data analysis and it was observed that the distribution was not normal. And so Wilcoxon Marked Rank Test was used to determine the development and skills of the groups themselves. The Mann-Whitney U test was used to assess the development of the experimental and control group in terms of pretest and posttest scores. Cronbach Alpha reliability analysis was also performed for the scales used in the research. According to research findings, there was a statistically significant difference between test and control groups posttest, self-efficacy values and life satisfaction values (p <0.05). As a result, verbal feedback given to handball players over a twelve-week training period was found to have a positive effect on self-efficacy and life satisfaction.